Functional properties of eyelid conditioned responses and involved brain centers - Parras, Gloria G.; Leal-Campanario, Rocío; López-Ramos, Juan C.; Gruart, Agnès; Delgado-García, José M. (Frontiers in Behavioral Neuroscience, 2022)
For almost a century the classical conditioning of nictitating membrane/eyelid responses has been used as an excellent and feasible experimental model to study how the brain organizes the acquisition, storage and retrieval of new motor abilities in alert behaving mammals, including humans. Lesional, pharmacological, and electrophysiological approaches, and more recently, genetically manipulated animals have shown the involvement of numerous brain areas in this apparently simple example of associative learning. In this regard, the cerebellum (both cortex and nuclei) has received particular attention as a putative site for the acquisition and storage of eyelid conditioned responses, a proposal not fully accepted by all researchers. Indeed, the acquisition of this type of learning implies the activation of many neural processes dealing with the sensorimotor integration and the kinematics of the acquired ability, as well as with the attentional and cognitive aspects also involved in this process. Here, we address specifically the functional roles of three brain structures (red nucleus, cerebellar interpositus nucleus, and motor cortex) mainly involved in the acquisition and performance of eyelid conditioned responses and three other brain structures (hippocampus, medial prefrontal cortex, and claustrum) related to non-motor aspects of the acquisition process. The main conclusion is that the acquisition of this motor ability results from the contribution of many cortical and subcortical brain structures each one involved in specific (motor and cognitive) aspects of the learning process.